Risk Assessment and Correlation Analysis of Potentially Toxic Element Pollution in Soil and Crops: A Case Study in a Typical Area - Jiufen Liu; Cang Gong; Yinji Ba; Shuliang Liu; Huiyun Wan; Xiaofeng Zhao; Ziqi Li; Xiaohuang Liu; Zhongfang Yang (Toxics)
Soil contamination with potentially toxic elements (PTEs) not only poses potential ecological risks (RI) but also leads to human health risks (HI) through the uptake of potentially toxic elements by crops. However, most studies primarily focus on potentially toxic element contamination in either soil or crops, often neglecting the intrinsic connections between soil and crop contamination risks. In reality, some regions may exhibit severe soil PTE exceedances, yet the PTE levels in crops may not necessarily exceed regulatory limits, resulting in human health risks that are not uniformly high. This study investigated a typical area with severe soil PTE pollution caused by wastewater from electroplating, smelting, and ore beneficiation industries, and conducted risk assessments on soil and crops. The research aims to elucidate the differences in soil and crop PTE contamination risks and the correlations between PTE concentrations in soil and crops. Results showed that Cd was the most severe PTE contaminant in the soil in the study area, with an average concentration of 1.11 mg/kg and a maximum concentration of 7.30 mg/kg. However, the average concentrations of eight PTEs in crops were all below the standard limits for cereal crops specified in the Food Safety National Standard for Pollutant Limits in Foods (GB 2726-2022). Cd was identified as the most severe PTE contaminant in the soil, resulting in the highest RI (836) in the MY sub-region of the study area. However, Cr in crops contributed the most to health risk (63.5%), leading to the highest HI (7.1) in sub-region MY. Despite Cd being the most severely polluting PTE in soil, its contribution to human health risk through crops was relatively low, ranging from 2.82% to 9.90%. This discrepancy in pollution risks indicates that a PTE causing severe soil contamination may not necessarily result in significant human health risks via crop uptake. Correlation and regression analyses revealed that soil PTEs had the greatest impact on Cd levels in crops. Soil Ni, Cd, Cu, As, and Zn exhibited different synergistic or antagonistic effects on crop PTE uptake. Notably, soil Cd content showed a highly significant positive regression relationship with Cd, Cr, and Ni concentrations in crops. Overall, the influence of soil PTEs on crop PTEs varied significantly, and the spatial differentiation characteristics of PTEs in soil and crops differed. For PTEs with high spatial differentiation, localized and precise management measures should be implemented. Conversely, for PTEs with low spatial differentiation, unified risk management and control measures can be adopted.